'It's just a virus' – viral illness in older people: prevention and management. Issue 2 (3rd April 2013) - Payne, Ruth; Forde, Donall; Vedio, Alicia; Cope, Alison; Pratt, Gary; Tunbridge, Anne
Summary: Many viral infections that cause minor illness in younger adults can lead to significant mortality and morbidity in older people, particularly as co-morbidities tend to accumulate with increased age. Respiratory and gastrointestinal viruses are ubiquitous and frequently cause outbreaks, with major impact on those in care homes or residential accommodation. Advances in medicine have opened the way for increased impact of the herpes viruses (varicella zoster virus, herpes simplex virus, Epstein–Barr virus and cytomegalovirus), as immune systems are manipulated. People are also leading more active lives in older age; human immunodeficiency virus (HIV) will be increasingly prevalent, as those living with HIV grow older in good health. In addition, new diagnoses of HIV, viral hepatitis and travel-related infections will present to those working in health care of older people. This review article of viral infections aims to highlight relevant pathology, with specific reference to management in older people.